Theoretical and methodological prerequisites for creating a construction organization system based on digitalization - Dubinin, D. (Ways to Improve Construction Efficiency, 2022)
The article reveals the theoretical and methodological principles of the formation of a modern construction organization system in the conditions of digital transformation of the construction sector of the economy. The main scientific approaches are analyzed, including systemic, adaptive, transformational, evolutionary and informational as fundamental frameworks for rethinking the traditional organizational structure of the construction process, which is completely transformed under the influence of digital technologies and new management tools. It is shown that modern challenges associated with increasing complexity of objects, multi-vector nature of participants, military risks, lack of investment and high requirements for quality and speed of implementation require an adaptive, integrated and digitally oriented construction management model. The paper outlines the key methods that form the basis of digital construction organization: modeling of development scenarios, optimization and expert methods, network and linear models, fuzzy set methods, simulation modeling. Promising directions of digitalization have been identified, in particular the introduction of BIM technologies, digital solutions, ERP systems, drones and robots for construction control, 3-D printers, as well as the use of artificial intelligence to automate management and organizational, technological and logistical solutions. It is substantiated that the theoretical and methodological modernization of the construction organization system should be based on a combination of general scientific, special and digital approaches, taking into account new technological capabilities. Such an approach ensures increased reliability, transparency, flexibility and stability of building systems, helps prevent destructive changes and allows for effective response to environmental challenges. The proposed theoretical and methodological foundations can be used as the basis for further research and practical models of digital management in construction.